Renal Tumor - Chen, Jindong (IntechOpen, 2013)
Summarizing a decade of scientific advance and therapeutic innovation, Renal Tumor offers all physicians treating kidney cancer, as well as researchers, updated information concerning the epidemiology, biology, and treatment of renal cell carcinoma. Contributors to this book are from all over the world and are experts in their individual fields. They have provided reviews about current knowledge in the management of both localized and metastatic renal cell carcinoma, as well as the latest developments in molecular genetics, imaging, and immune dysfunction associated with the diseases. Further special attention is paid to the biology of selected target molecules and various agents that inhibit these targets, including full chapters devoted to pharmaceutical drugs that selectively inhibit receptor tyrosine kinases, such as sunitinib and axitinib. Readers such as urological physicians, researchers, and kidney cancer patients are potential beneficiaries of this book.